2001
DOI: 10.1046/j.1365-2346.2001.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac preload by indicator dilution and transoesophageal echocardiography

Abstract: Within the observed range of data, intrathoracic blood volume and end-diastolic area are equivalent indices of cardiac preload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…In addition, Tousignant et al [24] found only a modest correlation between left ventricular end-diastolic area and SV, and they attributed this modest correlation to the fact that many patients in their study had chronic heart disease and reduced left ventricular function. In contrast, Buhre et al [35] showed in their study of 10 patients with 'healthy hearts' that both left ventricular end-diastolic area and intrathoracic blood volume represented valid parameters of ventricular preload. However, these were healthy individuals who were not receiving catecholamines.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, Tousignant et al [24] found only a modest correlation between left ventricular end-diastolic area and SV, and they attributed this modest correlation to the fact that many patients in their study had chronic heart disease and reduced left ventricular function. In contrast, Buhre et al [35] showed in their study of 10 patients with 'healthy hearts' that both left ventricular end-diastolic area and intrathoracic blood volume represented valid parameters of ventricular preload. However, these were healthy individuals who were not receiving catecholamines.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, echocardiographic measurements of CO and preload are themselves often the gold standard against which new cardiovascular devices are tested. 15,16 The SVR was calculated, and the IVC diameter and diameter change were added elements of the FREE, which may be especially useful in critically ill trauma patients. The fundamental difference between a FREE and a standard transthoracic examination is in how the data are presented, as a result, the FREE was able to answer the clinical question in 87% of patients.…”
Section: Discussionmentioning
confidence: 99%